Implementasi Model SIUUL dalam Pembelajaran Keterampilan Sebagai Pemandu Wisata Pada Mahasiswa Program Studi Manajemen - Amelia Alvina Dewi; Muhammad Daffanda Fadilla; Muhammad Renvil; Sherli Indah Lestari; Shintiana Rahman; Sri Watini (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The SIUUL (Simak-Ucap-Ulang) model is a systematic reading and speaking learning model based on Islamic values and based on human excellence as a creature of God Almighty who is given the logic of thinking and common sense with moral, religious and ethical values in harmony. The SIUUL (Simak-Ucap-Ulang) model is designed to improve skills in learning as well as being a tour guide. The purpose in making this research is to find out about the implementation of the SIUUL (Simak-Ucap-Ulang) model in learning management students as tour guides. The method used in this research is descriptive qualitative. The results of this study indicate that the application of the SIUUL (Simak-Ucap-Ulang) model is effective for learning management study program students in improving skills as tour guide.